La investigación criminal y la verdad procesal en el caso de María Mercedes Hurtado Álvarez (2014)
This time would be of great importance to develop a theme that culminates with the criminal investigation and that is embedded in a theoretical framework such as the procedural truth which is present during all stages, from the same criminal complaint or where the state puts news running all their criminal investigation apparatus according to protocols established mechanisms and pre Colombian law and the attorney general Manuel de la nation entity who retains full responsibility for criminal investigation, said it this way all begins officially to the report of the first respondent which is nothing more than the written account of the former reaching the scene, super important for any researcher stage, as described in this report every detail, so that in turn the researcher to receive the scene is fully aware of what happened or at least approach the offense or conduct possibly deployed, thus opening is given to the investigation of the case seeking the real truth, then pull up the procedural truth. The truth in a process is one of the essential purposes of any judicial authority and should be one of the most important for the implementation of the right either active part and passive part where those exercising investigative functions principles, through different types and applications of criminology broadcast their scientific and technical to the prosecutor for this in turn can determine guilt concepts, not guilt or otherwise or liability or criminal responsibility of a subject; therefore it is necessary that the litigants are put into the task of finding and practice each material evidence in due form and within legal terms, where from the provisions achieved on testing can be more effectively trial within a dynamic practice to get them for the judge to not lose focus and fairness at the time of its ruling